Supporting information for the research study: Niche divergence among members of the Amblyomma maculatum Koch, 1844 (Acari: Ixodidae) group of ticks [Conjunto de datos] - Cuervo, Pablo Fernando; Flores, Fernando Sebastián; Venzal, José Manuel; Nava, Santiago (2021)
Datos primarios de apoyo para el estudio de investigación titulado: Niche divergence among closely related taxa provides insight on evolutionary patterns of ticks, publicado en Journal of biogeography (First published: 08 September 2021)